2007
DOI: 10.1074/jbc.m701484200
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl-mediated Phosphorylation of WAVE3 Is Required for Lamellipodia Formation and Cell Migration

Abstract: The activity of the Wiskott-Aldrich syndrome-related WAVE3 protein is critical for the regulation of the Arp2/3-dependent cytoskeleton organization downstream of Rac-GTPase. The Ableson (Abl) non-receptor tyrosine kinase is also involved in the remolding of actin cytoskeleton in response to extracellular stimuli. Here we show that platelet-derived growth factor stimulation of cultured cells results in WAVE3-Abl interaction and localization to the cell periphery. WAVE3-Abl interaction promotes the tyrosine phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
122
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(134 citation statements)
references
References 37 publications
10
122
1
1
Order By: Relevance
“…1). Moreover, Mader et al 100 demonstrated that Arg localized to invadopodia and promoted EGFR/Src/cortactin-mediated matrix degradation, actin polymerization, invadopodia formation, and Matrigel transwell invasion of MDA-MB-231 cells, and Sossey-Alaoui and colleagues 101 showed that c-Abl not only promotes matrix degradation but also stimulates PDGF-directed motility of MDA-MB-231 cells via c-Abl-dependent phosphorylation of WAVE3 (Fig. 1).…”
Section: 97mentioning
confidence: 99%
See 1 more Smart Citation
“…1). Moreover, Mader et al 100 demonstrated that Arg localized to invadopodia and promoted EGFR/Src/cortactin-mediated matrix degradation, actin polymerization, invadopodia formation, and Matrigel transwell invasion of MDA-MB-231 cells, and Sossey-Alaoui and colleagues 101 showed that c-Abl not only promotes matrix degradation but also stimulates PDGF-directed motility of MDA-MB-231 cells via c-Abl-dependent phosphorylation of WAVE3 (Fig. 1).…”
Section: 97mentioning
confidence: 99%
“…One possibility may involve staining tumor serial sections with antibodies directed against (1) c-Abl and Arg to examine overall expression, (2) c-Abl/Arg substrates (e.g., Crk/CrkL, cortactin, WAVE3, galectin-3) 83,100,101,103,123,125,126 to indirectly examine kinase activity, and (3) proteins known to act downstream of c-Abl/Arg in a particular cancer type (e.g., STAT3, p38, p68, ERK5). 83,86,89,127 Alternatively, for tumor types containing low levels of stromal tissue and other non-tumor-associated cells, direct assessment of activity could be determined by kinase assay on tumor homogenates if enough sample is available.…”
Section: Clinical Targeting Of Abl Family Kinases In Solid Tumorsmentioning
confidence: 99%
“…Abl kinases are transiently activated by growth factors that stimulate RTKs and lead to actin cytoskeleton reorganization that is required for the formation of lamellipodial protrusions, membrane dorsal ruffles, cell migration, invasion, cell scattering and/or tubulogenesis (Boyle et al, 2007;Li et al, 2015;Plattner et al, 2003Plattner et al, , 1999. Abl-dependent regulation of cytoskeletal dynamics is mediated by the phosphorylation of target proteins, such as cortactin that is required for platelet-derived growth factor (PDGF)-induced dorsal membrane ruffles (Boyle et al, 2007), as well as actin nucleatingpromoting factors, such as N-WASP and WAVE proteins required for membrane protrusions (Burton et al, 2005;Miller et al, 2004;Sossey-Alaoui et al, 2007;Stuart et al, 2006). Abl kinases also transduce signals from cell surface receptors, such as integrins, cadherins, chemokine receptors and the T cell receptor (TCR), to reorganize the cytoskeleton.…”
Section: Structure Modular Domains and Enzymatic Regulation Of The Amentioning
confidence: 99%
“…Thus, a phosphatase is capable of controlling the extent and duration of signaling events via synergistic dephosphorylation of a kinase and its substrate. It is also important to note that, in addition to the direct regulation of Kette, PTP61F may participate in control of the actin cytoskeleton indirectly through inactivation of dAbl, which may phosphorylate SCAR/ WAVE for regulation of cell spreading, lamellipodium formation, and cell migration, as evidenced in mammals (43,46). If this is the case, to terminate such signaling cascades, PTP61F may simply dephosphorylate dAbl, thus downregulating the activity of SCAR/WAVE indirectly.…”
Section: Discussionmentioning
confidence: 99%